An approach for constructing mobile applications using service proxies - Hokimoto, A.; Kurihara, K.; Nakajima, T. (Proceedings of the 16th International Conference on Distributed Computing Systems, 2002)
In this paper, we propose software architecture using a notion of service proxies, that is a new framework for constructing applications in mobile computing environment. Our framework especially takes into account applications accessing services on Internet such as WWW browsers and MBONE conference tools. In our framework, an application is partitioned into two pieces, one piece runs on a mobile computer, and another piece runs on a stationary computer, where they are connected by wireless networks that may be replaced on the fly. The piece on a stationary computer is called a service proxy. The service proxy filters or caches data from servers before transmitting the data to the piece on a mobile computer. These two pieces are constructed by composing small objects whose composition can be dynamically reconfigured by adding or removing replaceable devices. The paper also presents a toolkit using our framework for building mobile applications easily.